Fluência e compreensão na leitura de textos: um estudo com crianças do 4º ano do ensino fundamental - Puliezi, Sandra (2015)
Current studies about reading show that there is a strong relationship between comprehension and reading fluency, to the extent that one influences another. In order to contribute to the growth of this knowledge, we conducted a study to investigate the relationship between reading comprehension and reading fluency of Brazilian children who attend the 4th year of elementary school. Objectives of this research were: verify the effects of an intervention in comprehension; verify the effects of an intervention in reading fluency; and create a series of activities for the improvement and stimulation of reading fluency and comprehension. To accomplish these objectives, we created two intervention groups (one in fluency and the other in comprehension) and a control group. At the beginning of the school year all the groups completed two tests: an assessment of fluency (accuracy, speed and prosody) and an assessment of comprehension. The intervention lasted three months. At the end of that time, every group completed the same assessments of fluency and comprehension, plus a test to evaluate inferential comprehension. We then analyzed the data to compare student performance between the three groups. The results showed that interventions helped to improve the performance of students in the skills that were being targeted, but not the other skill. Pearson's correlations allowed us to see that high performance in comprehension is accompanied by high performance in fluency, highlighting the importance of the two skills for success in reading. Our study indicated the need to direct teaching in order to fully develop the three dimensions of fluency and the different levels of comprehension, leading us to conclude that the teaching of one of these skills alone does not ensure success in the other